Health-Related Quality of Life in a Slovak Representative Sample: A Validation Study of the Short Form-8 Scale - Purova, Dana; Furstova, Jana; Kascakova, Natalia; Dobrotkova, Alena; Sigmundova, Dagmar; Hasto, Jozef; Tavel, Peter (Value in health regional issues, 2025)
OBJECTIVES: The Short Form-8 (SF-8) is a widely used 8-item tool for health-related quality of life assessment. This study aimed to evaluate the psychometric properties of the Slovak version of the SF-8 in a population sample. METHODS: A cross-sectional survey on a Slovak representative sample (n = 1018; mean age 46.24 ± 16.56 years; 51.3% women) monitoring health and well-being was performed in 2019. Exploratory network analysis and confirmatory factor analysis were used to assess the construct validity of the scale. Reliability and sociodemographic differences were evaluated. RESULTS: A 2-factor model had an adequate fit to the data [χ2(19) = 186.2, P < .001, comparative fit index = 0.998, Tucker-Lewis index = 0.997, root mean square error of approximation = 0.093, standardized root mean of residuals = 0.039], with high reliability (α = 0.93, ω = 0.95). The physical component score and mental component score (MCS) were negatively associated with the presence of chronic health conditions. Lower physical component score and MCS were associated with higher age (P < .001), and lower MCS were associated with female gender (P < .001). CONCLUSIONS: The Slovak version of the SF-8 represents a valuable tool for measuring health-related quality of life in the Slovak population in both practice and research.
Keywords: senioři; Psychometrics; Reproducibility of Results; Cross-Sectional Studies; psychometrie; reprodukovatelnost výsledků; Middle Aged; průzkumy a dotazníky; mužské pohlaví; průřezové studie; Adult; kvalita života; Slovakia; Slovenská republika; ženské pohlaví; Humans; Surveys and Questionnaires; lidé středního věku; Health Status; dospělí; zdravotní stav; Quality of Life; Female; Aged; lidé; Male